Energy saving analysis of air fan motor in power plant boiler controlled by variable frequency drive - Pramono Mukti Wibowo; Muhamad Haddin; Arief Marwanto (International Journal of Power Electronics and Drive Systems (IJPEDS), 2021)
A reporting of Energy Audit in 2018 by LEMTEK UI has reported that air fan system currently used in Power Plant of PLTU Tanjung Jati B Jepara is inefficient, energy efficiency in FDF is only 32% and PAF efficiency is 49.01%. Inefficiency of the air fan system is an impacted there are waste of electric energy amount of 13,352,929 KWh (13,35 GWh) a year with a financial loss of IDR 13,352,929,140. To overcome this condition, variable frequency drive (VFD) is installed which adjusted air flow as needed so that energy waste can be reduced. MATLAB simulation is proposed to analyze the VFD method. The result shows that by using VFD, 8,233,573.444 KWh (8.45 GWh) can be saved a year. Total cost benefits are IDR 8,233,573,444 as 32.1% of saving cost. Efficiency of FDF is 72.57 % and PAF is 66.84%.